Changes to the ART guidelines - an overview - Celicia Serenata (AOSIS, 2010)
In 2009 the South African National AIDS Council (SANAC) Treatment Technical Task Team (TTT) finalised recommendations for changes to the national standard treatment guidelines for adult and paediatric management and treatment, as well as changes in the prevention of mother-to-child transmission of HIV (PMTCT) guidelines, moving away from monotherapy to dual therapy. President Zuma announced changes in the national antiretroviral therapy (ART) programme on World AIDS Day 2009. Subsequently additional changes were made to the treatment guidelines to be in line with these new Presidential mandates, which came into effect on 1 April 2010.